Solvent Extraction Studies for the Separation of Trivalent Actinides from Lanthanides with a Triazole-functionalized 1, 10-phenanthroline Extractant. Issue 7 (9th November 2020) - Zsabka, Peter; Opsomer, Tomas; Van Hecke, Karen; Dehaen, Wim; Wilden, Andreas; Modolo, Giuseppe; Verwerft, Marc; Binnemans, Koen; Cardinaels, Thomas
ABSTRACT: A new N -atom donor extractant 2, 9-bis(1-(2-ethylhexyl)-1 H -1, 2, 3-triazol-4-yl)-1, 10-phenanthroline (EH-BTzPhen) was synthesized and used in solvent extraction studies to separate the trivalent minor actinide americium(III) and curium(III) from europium(III), representing fission product lanthanides. The extractant was found to be soluble in 1-octanol and in the Aliquat-336 nitrate ([A336][NO3 ]) ionic liquid diluent, but insoluble in n -dodecane. The [A336][NO3 ] is a fully incinerable room temperature ionic liquid, and has a higher flash point than aliphatic diluents such as 1-octanol. The EH-BTzPhen proved to be effective for selective minor actinide extraction only in combination with 2-bromohexanoic acid synergist when 1-octanol was used as a diluent ( SF Am/Eu > 200). The change of the diluent from 1-octanol to Aliquat-336 nitrate allowed selective An(III) extraction from low acidity feed solutions without the need of a synergist ( SF Am/Eu 70 and SF Am/Cm 1.9–2.2). The phase transfer kinetics of the ligand-metal complexes is however very slow at 22 °C in the case of both solvents. With this newly synthesized extractant, the achieved SF Am/Cm was comparable to the values achieved with the established CyMe4 BTBP and CyMe4 BTPhen extractants.